Investigations of formation of chatter in a non-wavy surface during thread cutting and turning operations - Anayet Ullah Patwari, Mohammed; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Ishtiyaq, M. H. (Trans Tech Publications, Switzerland, 2010)
An attempt has been made to investigate the chatter formation during two machining operations namely, turning and thread cutting on a non-wavy surface of plain carbon steel with a view to observing the formative mechanisms of chatter. Investigations have been conducted on the chips and common types of discreteness in the form of serrated/saw teeth have been identified. Mechanisms of formation of these teeth have been studied and the frequencies of their formation have been determined at different cutting speeds. The different modes of the vibrating components have been extracted by modal analysis and the vibration responses during cutting conditions have also been recorded using an online data acquisition system. All the experiment were conducted on a no wavy surface and thread cutting was conducted on nascent surface, the existence of chatter observed during the experiments prove that the regenerative effect from the waviness of the previous pass, as postulated by the ‘Regenerative Chatter Theory’ is not correct in explaining the primary cause of chatter during metal cutting. The analysis of amplitude of chatter during machining indicates that noticeable chatter appears in the system when the chip serration frequency is equal to or integer multiple of the prominent natural frequency of the system components.